Circulating neonatal Nav1.5 (nNav1.5) antigen and anti-nNav1.5 antibodies as potential biomarkers for breast cancer metastasis - Harishini Rajaratinam,; Nur Syahmina Rasudin,; Maya Mazuwin Yahya,; Wan Zainira Wan Zain,; Sabreena Safuan,; Nurul Asma-Abdullah,; Noor Fatmawati Mokhtar,; Wan Ezumi Mohd Fuad, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Neonatal Nav1.5 (nNav1.5) has been known to potentiate breast cancer (BCa) metastasis. The detection of anti-nNav1.5 antibodies (anti-nNav1.5-Ab) reflects the immunogenicity of nNav1.5. However, the presences of circulating nNav1.5 antigen and anti-nNav1.5-Ab in the context of BCa metastasis have not been explored yet. Therefore, the study has attempted to conduct such an investigation using both blood samples from 4T1 orthotopic mice and BCa patients. In the preclinical study, forty female BALB/c mice were divided into three groups: 4T1 orthotopic BCa mice (n=17), control mice (n=20) and positive control mice (n=3). After tumour development, the mice were sacrificed to obtain target organs, whole blood, and serum. Histopathology, cytokine analyses, real-time PCR, and indirect ELISA were performed. Histopathology and cytokine analyses showed the establishment of metastasis in 4T1 orthotopic mice. The concentration of vascular endothelial growth factor (VEGF) was significantly higher in the 4T1 orthotopic mice (P<0.0001****). Circulating nNav1.5 antigen and anti-nNav1.5-Ab were detected in 4T1 orthotopic mice, using real-time PCR and indirect ELISA, respectively. Furthermore, there was an inverse relationship between anti-nNav1.5-Ab and the total metastatic foci (P=0.0485*, r=-0.7306). In the clinical study, 32 BCa patients were grouped based on their stages: early-invasive (n=15) and advanced (n=17) stages. Approximately 3 mL of blood was withdrawn, and only indirect ELISA was conducted. The clinical study showed that BCa patients of advanced-stages portrayed higher expression of anti-nNav1.5-Ab compared to early stages of BCa (P =0.0110*). In conclusion, the detection of nNav1.5 antigen and anti-nNav1.5-Ab was consistent with the presence of BCa metastasis.